Pendidikan Kewirausahaan dalam Meningkatkan Life Skill Santri di Pondok Pesantren Al-Karimiyyah Bodak Barat Lombok Tengah - Paska Dinata; Yudin Citriadin; Badrun Badrun (Manajemen Pendidikan Islam STIT Palapa Nusantara, 2023)
This research started with the absence of a place for students to channel their talents and interests when they were at Islamic boarding schools. Entrepreneurship education is very important as a provision for students when they become alumni. This study aims 1) To find out the types of entrepreneurship developed at the Al-Karimiyyah Islamic Boarding School 2) How is the process of entrepreneurship education to improve the life skills of students 3) To know the values of entrepreneurship at Al-Karimiyyah Islamic Boarding School Bodak West Lombok, Central Lombok. This research is a qualitative research, the data collection used is observation, interviews and documentation. Data analysis uses the Miles and Huberman model, which is an interactive model analysis with the steps: data collection, data condensation, data display, and data verification. The results showed 1) Entrepreneurship Education in Al-Karimiyyah Islamic Boarding School Bodak West Lombok, Central Lombok is divided into 5 types of entrepreneurship, including: catering, animal husbandry, plantation, handicrafts and printing. 2) The process of entrepreneurship education and life skills has been running smoothly and is developing due to the support and cooperation of all Islamic boarding schools. 3) Entrepreneurial values seen in improving the life skills of students at Al-Karimiyyah Islamic Boarding School Bodak West Lombok, Central Lombok include: a) . Honest and trustworthy b). Creative c). Professional d). dynamic e). Cooperation f). hard work g). Responsible h). Persevere and tenacious.